Fenologia, qualidade de diásporos de Myracrodruon urundeuva e banco de sementes em áreas de caatinga - Azevedo, Aderdilânia Iane Barbosa de (2016)
Myracrodruon urundeuva as a result of its multiple uses is subject to intense predatory processes of exploitation, causing the decrease of its natural populations. Due to its importance for the conservation of the natural landscape of the caatinga and the use of native species for reforestation and sustainable management programs, this research was carried out in three stages, aiming to: (i) characterize the phenological phases of Myracrodruon urundeuva, and its relationship with the temporal distribution of rainfall pulses in areas of the paraibano‟s cariri; (ii) analyze the physiological quality of diasporas from mother trees of Myracrodruon urundeuva in different areas of the paraibano‟s cariri and (iii) evaluate the seed bank in two areas of occurrence of Myracrodruon urundeuva in the paraibano‟s cariri. For the phenology 78 mother plants were selected in an area located in São João do Cariri and two areas in Boa Vista, PB, and evaluated by the method of the percentage of Fournier and activity index. In the same areas diasporas of different mother trees were collected and transported to the Seed Analysis Laboratory, CCA, UFPB for analysis of the physiological potential. In addition, soil samples from two areas in each city were collected at 1 and 10 m from the base stem of each mother plants following the north, south, east and west directions. From the results it was found that phenophases of budding, senescence, flowering and fruiting in M. urundeuva occur in synchrony with the temporal distribution of rainfall in the areas of its occurrence. The intensity and duration of phenological phases of development of M. urundeuva depend on the amplitude and frequency of rainfall pulses during the rainy season. The phenological distribution events of Aroeira have seasonal distribution during the life cycle and are more uniform in the senescence. The total senescence of leaves of M. urundeuva happens when rainfall interpulse intensify as the dry season progresses, featuring deciduous. The variation of physiological quality of diasporas of M. urundeuva is dependent on environmental factors and varies from mother plants, areas and years of collecting. It is necessary more than one area to collect diaspores from mother plants of M. urundeuva, being the plants of the groups 1 and 2 promising to contain representatives of the three areas and producing diaspores with high physiological potential. In the studied areas the seed bank has similar floristic composition with predominance of herbaceous species.